Legacy base metal slags can generate toxic leachates. (30th January 2018) - Awoniran, Adijat T.; Ketheson, Annelly; Piazolo, Sandra; Gore, Damian B.
Abstract : Slags sourced from a derelict zinc–lead–copper–silver–tungsten mine were examined for their bulk elemental composition and mineralogy. pH, oxidation–reduction potential, and the leachability of selected elements (sulphur, calcium, iron, copper, zinc, and lead) were assessed during a 130-day deionised water extraction conducted under oxic conditions. Slags were rich in silicon, iron, copper, zinc, and lead, hosted within minerals including quartz (SiO2 ), goethite [FeO(OH)], augite [Ca(Mg, AI, Fe)Si2 O6 ], and lead (Pb 0 ). Leachates from the slags increased in analyte concentration throughout the 130-day experiment, with iron, copper, zinc, and lead attaining >5 mg l − 1 in some samples. These findings indicate that this pyrometallurgical waste should not be considered environmentally inert, as leachates emanating from them in the field might pose a significant risk to the environment.